Auditoría financiera y los resultados de la gestión económica de la empresa comercial agrícola piedacita año 2012 - Maldonado Briones, Yenifher Anaïs (2014)
thesis was made in Piedacita Agricultural Trade Company , located at Avenida Fajardo Walter Andrade S / N, Tenth intersection, next to Hotel Costa del Sol Citadel The Drivers, October parish Seven Region Quevedo, The Province rivers , in order to apply the financial audit to determine the results of the economic management of the company, it was necessary to analyze the degree of reliability of the accounting system, just as the degree of reasonableness that the financial statements present was determined and finally the economic management that the company developed in the period 2012 was examined. Two types of research were used, field , implemented in the offices of Agricultural Piedacita, technical surveys and interviews were applied to staff and administrators of the estate, the kind of research was literature - documentary, plus several methods were used; inductive, deductive and analytical, which allowed to collect primary and secondary information according to topic. The purpose of the study was to determine the level of confidence it gave 72% control and a risk of 28%. Showing that the control of your assets is high. With this thesis hopes and aims to improve economic management Piedacita Agricultural trading company, through the implementation of efficient accounting processes and the adoption of accounting standards. The DuPont System provided a return of 26% for 2011 and 49%